Community Participation in Sustainable Tourism: A case study in Balige, Indonesia - Ginting, Nurlisa; Munazirah; Wahid, Julaihi (Environment-Behaviour Proceedings Journal, 2023)
The current tourism industry always incorporates the concept of sustainability. Escalating the economy of a region is achievable by employing sustainable tourism. Balige is a priority destination on the national development agenda. Community participation may promote various aspects of sustainability, including the economy. This research aims to determine what forms of community participation can be employed to develop the economy. This study utilizes a mix of quantitative and qualitative methods. The data was collected through questionnaires, interviews, and observations. The research concludes with recommendations to develop the economy through community participation, helping to achieve sustainable tourism in Balige.